“De Moelijike Middenweg”: Association Politics between the Dutch East Indie and the Netherlands through Indische Toneel, 1913-1933 - Nugroho, Khairana Zata; Sulistiyono, Singgih Tri; Puguh, Dhanang Respati (Indonesian Historical Studies, 2023)
This article discusses the endeavors to build a harmonious relationship between the colony of the Dutch East Indies and the motherland, the Netherlands, through the association politics in Indische toneel (Indies play) performances of Karina Adinda and Boeddhakind in 1913-1933. In the midst of the natives movement, where the natives put in motion their thoughts and ideas against the oppressive colonial government, a new cultural consciousness that desired a dialogue between East and West also appeared as the consequences of the implementation of the Dutch Ethical Policy. One of its aspects was performing art. Through historical method, this anomaly is examined through the performances of two Indische toneel namely Karina Adinda and Boeddhakind, Indische toneel that combined West dramaturgy with Javanese performances such as gamelan and traditional dances. The performances were produced in cooperation with organizations such as Vereeniging Oost en West, Het Nederlandsch-Indonesisch Verbond van Jongeren-Organisaties (NIVJO), and other Indonesian students in the Dutch East Indies and the Netherlands. The performances garnered disapproval from nationalists and praise from ethnicists